Evalvacija zdravstvenovzgojnega programa Šole za starše - Donko, Jana (Obzornik zdravstvene nege, 2003)
The article presents a research study performed in the years 2001/2002 on a sample of 30 pregnant women in the second part of their pregnancy. They participated in the "school for parents" program "preparation for childbirth".The goal of the research was fo find out which pregnant women takepart in the course, whether or not are they suffuciently informed about it, their motive for participation, their previous knowledge, what they learn during the course and their opinion about it. The results revealed that participant are mostly primiparae with high school education, well informed about the organization of the course; their main motive was to enhance their knowledge which is insufficient prior to course. The majority of women are satisfied with the course. In conclusion, certain ideas to make the course better and more interesting, are hinted at.
Keywords: ankete; childbirth; Health Education; human pregnancy; Labor; Nosečnost; Parents; Porod; Pregnancy; Questionnaires; Starši; Zdravstvena vzgoja